1994
DOI: 10.3109/08916939409007997
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Nuclear, Anti-Neutrophil Cytoplasmic and Anti-Glomerular Basement Membrane Antibodies in Hiv-Infected Individuals

Abstract: Many autoantibodies have been described in HIV-infected individuals. We have examined the incidence, associations and prognostic significance of anti-nuclear antibodies (ANA), anti-neutrophil cytoplasmic antibodies (ANCA) and anti-glomerular basement membrane (GBM) antibodies in individuals with HIV infections. One hundred and five patients, with asymptomatic infections (n = 37), AIDS-related complex (n = 32) or AIDS (n = 36) were studied. Plasma from 24 of these (23%) were positive for ANA: most demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
4
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 25 publications
3
52
4
1
Order By: Relevance
“…Some findings reinforce the idea that the association described in this case is not casual, such as: crescentic glomerulonephritis is not common in HIV-positive patients [26], anti-GBM glomerulonephritis is rare and anti-GBM antibodies are frequently observed in HIV-positive subjects when compared to the overall population [26].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Some findings reinforce the idea that the association described in this case is not casual, such as: crescentic glomerulonephritis is not common in HIV-positive patients [26], anti-GBM glomerulonephritis is rare and anti-GBM antibodies are frequently observed in HIV-positive subjects when compared to the overall population [26].…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, Savige et al [26] found anti-GBM antibodies in 17% of HIV-positive patients, with a significant correlation between the presence of the antibody and CD 4 counts lower than 400/mL. Also, antinuclear antibodies were found in 23% and ANCA in 17% of the HIV-positive subjects.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, although antineutrophil cytoplasmic antibodies (ANCA) are frequently found in the sera of HIV-positive patients, with a frequency varying from 18 to 41.0%, no correlation has been found between ANCA positivity and the presence of clinically active vasculitis in these patients [22,23,24]. In the majority of these cases, immunofluorescence reveals an atypical ANCA pattern.…”
Section: Hiv-infected Patients With Kidney Disease Other Than Hivanmentioning
confidence: 99%
“…5 O papel direto das partículas virais, os complexos imunes gerados, a desregulação na interação de linfócitos B/T, 6 o mimetismo molecular, 7 a ativação policlonal de linfócitos B poderiam favorecer a síntese de auto-anticorpos, que estão presentes em 23% dos pacientes infectados pelo VIH. 8 Segundo Iordache L et al estas doenças auto-imunes ocorrem sobretudo no contexto de bom controle imunológico (uso de TARV), como no presente caso, e mesmo durante a síndrome de reconstituição imune. 9 Outros autores consideram esta associação casual, em face da prevalência significativa de infecção pelo VIH e a raridade da concomitân-cia com doença autoimune.…”
Section: Discussionunclassified